Elemental Ratios Link Environmental Change and Human Health - Paseka, Rachel E.; Bratt, Anika R.; MacNeill, Keeley L.; Burian, Alfred; See, Craig R. (Frontiers in Ecology and Evolution, 2019)
Humans have fundamentally altered the cycling of multiple elements on a global scale. These changes impact the structure and function of terrestrial and aquatic ecosystems, with many implications for human health. Most prior studies linking biogeochemical changes to human health have evaluated the effects of single elements in isolation. However, the biological impact of shifts in the concentration of a single element often depend on its relative balance with other elements. This balance among multiple elements is the focus of ecological stoichiometry, which highlights the importance of elemental ratios in biological function across all systems and scales of organization. Consequently, ecological stoichiometry is a promising framework to inform research on the links between global changes to elemental cycles and human health. We synthesize evidence that elemental ratios link global change with human health through biological processes occurring at two scales: in the environment (natural ecosystems and food systems) and within the human body. Elemental ratios in the environment impact the key ecosystem processes of productivity and biodiversity, both of which contribute to the production of food, toxins, allergens, and parasites. Elemental ratios in diet impact processes within the human body, including the function and interactions of the immune system, parasites, and the non-pathogenic microbiome. Collectively, these stoichiometric effects contribute to a wide range of non-infectious and infectious diseases. By describing stoichiometric mechanisms linking global change, ecological processes, and human health, we hope to inspire future empirical and theoretical research on this theme.